On the Convergence of Affective and Persuasive Technologies in Computer-Mediated Health-Care Systems - Betances, Rebeca; Fico, Giuseppe; Salvi, Dario; Ottaviano, Manuel; Arredondo, María (Human Technology, 2015)
This paper offers a portrayal of how affective computing and persuasive technologies can converge into an effective tool for interfacing biomedical engineering with behavioral sciences and medicine. We describe the characteristics, features, applications, present state of the art, perspectives, and trends of both streams of research. In particular, these streams are analyzed in light of the potential contribution of their convergence for improving computer-mediated health-care systems, by facilitating the modification of patients' attitudes and behaviors, such as engagement and compliance. We propose a framework for future research in this emerging area, highlighting how key constructs and intervening variables should be considered. Some specific implications and challenges posed by the convergence of these two technologies in health care, such as paradigm change, multimodality, patients' attitude improvement, and cost reduction, are also briefly addressed and discussed.